A skin-core debonding quantitative algorithm based on hexagonal units reconstruction for air-coupled ultrasonic C-scan images of honeycomb sandwich structure. (September 2022) - Zhang, Hui; Liu, Si; Rui, Xiaobo; Zhu, Xiaoxi; Sun, Jing
Highlights: Debonding boundary can be identified inside units by fuzzy clustering anddivision for units. The unit array is clearly depicted based on the signals amplitude received at different structures. The detection efficiency is improved by the reduced dependence on the scanning step. Abstract: Honeycomb Sandwich Structure (HSS) is widely used in the aerospace industry. The skin-core debonding in HSS can grow to reach a critical size, leading to the sudden failure of structures. Due to the blurry edges on the C-scan image caused by honeycomb units with periodic honeycomb walls, accurate quantification of debonding is still a challenge. In this paper, accurate debonding quantification of HSS based on air-coupled ultrasonic C-scan and hexagonal units reconstruction is proposed. The debonding boundary identification is accurate to the interior of the honeycomb units by partial debonding units division based on calculating the total amplitude of all scanning points within the unit. The detailed process was presented with key steps as ultrasonic air-coupled C-scan for HSS, hexagonal units reconstruction based on peak points on C-scan images, units classification by K-means clustering algorithm, and units division according to the total amplitude. Four types of debonding, including film sticking, adhesive removal, slight subsidence, and severe subsidence, are used to evaluate the effectiveness of the method. The results show that the proposed method can describe and quantify-four kinds of debonding defects reliably and it is ideally suited for air-coupled ultrasonic C-scan image processing of periodic structures.